2013
DOI: 10.1186/1757-2215-6-18
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs overexpressed in ovarian ALDH1-positive cells are associated with chemoresistance

Abstract: BackgroundOvarian carcinoma is the leading cause of cancer death worldwide among gynecological malignancies, and the majority of cases are related with recurrence and chemoresistance. Cancer stem cells (CSCs) are believed to be one of the causes of recurrent or chemoresistant ovarian cancer, and microRNAs are regulatory molecules newly implicated to control a variety of cellular processes, including CSCs. Therefore, we identified ovarian CSC-specific microRNAs and investigated their clinicopathological implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
4
48
0
2
Order By: Relevance
“…Functional analyses by gene knockdown and a chemical inhibitor revealed that ALDH and SOX2 are essential for the proliferation of ovarian CSCs. Of note, both ALDH1A and SOX2 expression contribute to chemo-resistance of ovarian cancer cell lines (35,(43)(44)(45). Therefore, SOX2 and ALDH may mediate its capability to confer chemo-resistance to ovarian CSCs as well as stem cell-related features.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses by gene knockdown and a chemical inhibitor revealed that ALDH and SOX2 are essential for the proliferation of ovarian CSCs. Of note, both ALDH1A and SOX2 expression contribute to chemo-resistance of ovarian cancer cell lines (35,(43)(44)(45). Therefore, SOX2 and ALDH may mediate its capability to confer chemo-resistance to ovarian CSCs as well as stem cell-related features.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo model, they found that engineered knockdown of miRNA27b substantially repressed breast cancer growth in mice and increased miRNA27b levels correlate with poor treatment outcomes. Park et al (2013) showed that miRNA-27b is overexpressed in ovarian ALDH1-positive cells and associated with chemoresistance and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Six miRNAs, including miR-23b, miR-27a, miR-27b, miR-346, miR-424, and miR-503, were overexpressed in ovarian ALDH1-positive cells, and they were significantly upregulated in chemoresistant ovarian cancer cells and tumor samples compared with chemosensitive group. High ALDH1 expression was associated with chemoresistance in in vitro and ex vivo samples [26]. Besides, miR-200 family [27][28][29][30], miR-199/214 cluster [31][32][33][34][35], miR-31 [36] et al, are also reported to be connected with chemotherapy resistance, including cisplatin and pactitaxel (Table 1).…”
Section: Micrornasmentioning
confidence: 97%